Are evidence-based criteria addressed during counseling on over-the-counter products? An observational study in community pharmacies. Issue 11 (November 2021) - Moritz, Katharina; Seiberth, Jasmin Mina; Herrmann, Nia Sophie; Bertsche, Thilo; Schiek, Susanne
Abstract: Objective: We examined whether evidence-based criteria were addressed during counseling on over-the-counter products (OTCs) in community pharmacies. Methods: Consultations were observed in 10 community pharmacies. We analyzed communications about OTCs to determine if any information on three evidence-based criteria (outcome variables: scientific evidence such as clinical study results, pharmaceutical staff's experience, and customer's experience) was mentioned. Two groups of communications were compared with Pearson's chi-square and Fisher's exact test, as appropriate: The communications about OTCs recommended by the pharmaceutical staff vs. the communications about OTCs requested by customers. Results: In 379 observed consultations, 300 OTCs were recommended by staff and 390 OTCs were requested by customers. The least included criterion was scientific evidence (in OTCs recommended by pharmaceutical staff – 1% vs. requested by customers – 0%), followed by pharmaceutical staff's experience (5% vs. 1%). The customer's experience was addressed more frequently (14% vs. 41%). Statistically significant differences between the two groups were found for all criteria (p < 0.05). Conclusion: Evidence-based criteria were rarely addressed during counseling on OTCs. Practice implications: Pharmaceutical staff should be encouraged to include the three evidence-based criteria more frequently. Additionally, customers should be encouraged to request such information from the staff in community pharmacies. Highlights: Evidence-based criteria for OTCs were rarely addressed in pharmacy consultations. The least addressed criterion was the scientific evidence. The customer's experience was addressed most frequently. Communications for customer-requested OTCs differed from those recommended by staff.